Meningococcal Disease-Associated Prophage-Like Elements Are Present in Neisseria gonorrhoeae and Some Commensal Neisseria Species. (7th February 2020) - Al Suwayyid, Barakat A; Rankine-Wilson, Leah; Speers, David J; Wise, Michael J; Coombs, Geoffrey W; Kahler, Charlene M
Abstract: Neisseria spp. possess four genogroups of filamentous prophages, termed Nf1 to 4. A filamentous bacteriophage from the Nf1 genogroup termed meningococcal disease-associated phage (MDA φ) is associated with clonal complexes of Neisseria meningitidis that cause invasive meningococcal disease. Recently, we recovered an isolate of Neisseria gonorrhoeae (ExNg63) from a rare case of gonococcal meningitis, and found that it possessed a region with 90% similarity to Nf1 prophages, specifically, the meningococcal MDA φ. This led to the hypothesis that the Nf1 prophage may be more widely distributed amongst the genus Neisseria . An analysis of 92 reference genomes revealed the presence of intact Nf1 prophages in the commensal species, Neisseria lactamica and Neisseria cinerea in addition to the pathogen N. gonorrhoeae . In N. gonorrhoeae, Nf1 prophages had a restricted distribution but were present in all representatives of MLST ST1918. Of the 160 phage integration sites identified, only one common insertion site was found between one isolate of N. gonorrhoeae and N. meningitidis . There was an absence of any obvious conservation of the receptor for prophage entry, PilE, suggesting that the phage may have been obtained by natural transformation. An examination of the restriction modification systems and mutated mismatch repair systems with prophage presence suggested that there was no obvious preference for these hosts. A timed phylogeny inferred that N. meningitidis was the donor of the Nf1 prophages in N. lactamica and N. gonorrhoeae . Further work is required to determine whether Nf1 prophages are active and can act as accessory colonization factors in these species.